2016
DOI: 10.9778/cmajo.20150089
|View full text |Cite
|
Sign up to set email alerts
|

Does where you live matter? Leisure-time physical activity among Canadian youth: a multiple cross-sectional study

Abstract: Background:The aim of this study was to explore the population-wide distribution in the practice of leisure-time physical activity among Canadian youth and how physical activity level is influenced by contextual features of the environment. Methods:We studied the self-reported leisure-time physical activity of 54 832 Canadians aged 12 to 17 years. Observations were structured according to a 4-level geographic hierarchy. The outcome studied was a dichotomous indicator that referred to achieving (or not) the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Living in rural areas was treated as the referent category for all analyses. We used a model-building approach that added individual, socioeconomic, and seasonal covariates based on theoretical knowledge of potential confounding variables as has been done previously [ 16 ]. Interaction terms between location (urban versus rural) and sex were used to assess whether the associations between location and the odds of meeting the PA, screen time or both recommendations differed by sex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Living in rural areas was treated as the referent category for all analyses. We used a model-building approach that added individual, socioeconomic, and seasonal covariates based on theoretical knowledge of potential confounding variables as has been done previously [ 16 ]. Interaction terms between location (urban versus rural) and sex were used to assess whether the associations between location and the odds of meeting the PA, screen time or both recommendations differed by sex.…”
Section: Methodsmentioning
confidence: 99%
“…In Canada, self-reported data from earlier cycles of the Canadian Community Health Survey (CCHS), showed only rural-dwelling girls but not boys were more likely to meet the PA recommendation compared to those from urban communities [ 16 ]. Harvey et al (2017) [ 17 ] showed that Canadian children attending schools in larger urban settings were more likely to meet the PA recommendation than those attending schools in smaller urban or rural settings, whereas device-measured data by Nyström et al (2019) [ 18 ] indicated no significant differences in MVPA between urban and rural Canadian children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subgroup analysis was not performed due to insufficient power in each geographic region. Such analysis would also not be meaningful as it does not account for seasonal participation in physical activity, daylight hours [ 33 ], and other geographic factors (rural vs. urban) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%